Water canal use for the implementation and efficiency optimization of photovoltaic facilities: Tajo-Segura transfer scenario. (March 2016) - Colmenar-Santos, Antonio; Buendia-Esparcia, Ángel; de Palacio-Rodríguez, Carlos; Borge-Diez, David
Graphical abstract: Highlights: The technology of photovoltaic power plants on top of water canals is reviewed. A solution for the optimal distribution for linear configurations is presented. The solar plant for the Tajo-Segura canal is studied and benefits are calculated. Savings on water account for 226 k€/year and PV losses are reduced 6.57 GW h/year. Payback time for the investment is below 15 years. Abstract: The purpose of this paper is to prove as possible the improvement of the efficiency of a photovoltaic power plant, if it could be installed on top of a water canal, and how this facility could at the same time improve the efficiency of the water canal. The Tajo-Segura water transfer located in Spain has been chosen as the scenario for this research paper. The use of a water canal for this type of photovoltaic facility involves several problems. For example, it is very important that under no circumstance should any change on the canal structure affect the main end-use purpose of the hydraulic infrastructure (to channel water). Moreover, these facilities are strongly linear structures, so there is a problem connecting the electricity to the network. Nevertheless, these problems could be solved or minimized by applying different technical solutions, and if optimal synergies between infrastructures were obtained. It should be taken into account that the water facilities, which are already on service, save a significant quantity of water, and that these savings are achieved while avoiding the evaporation produced by direct solar radiation. The facility in this study can increase its efficiency, thanks not only to the optimal positioning to avoid the shadow between panels but also because panels can be cooled with the water that the canal contains. Focusing on these improvements, different types of technology implementation have been studied, concluding that the best option is the fixed system technology. A special methodology to geometrically place the photovoltaic panels has been developed. A proposal for novel cooling is also included in this work. The results of this study show that the project could be developed with an investment of 248 M€. Through the power generation and the savings in canal water resources, the investment could be repaid in approximately 15 years. The contribution of this work is the demonstration of the technical and economic interest of the optimal configuration analyzed.